Historical experience - Carr, David, 1940- author.
1 online resource (viii, 175 pages).
Keywords: "This volume brings together a collection of recent essays on the philosophy and theory of history. Phenomenology is about experience. In our language, "history" usually means either 1) what happened, i.e. past events, or 2) our knowledge of what happened. We can't experience past events, and whatever knowledge we have of them must come from other sources-memory, testimony, physical traces. Through these essays, the author explains how we can experience historical events. Sitting at the intersection of philosophy and history, this is the ideal volume for those interested in experience from a philosophical and historical perspective"--